'It is a different type of learning'. A survey-based study on how simulation educators see and construct observer roles. (5th September 2020) - O'Regan, Stephanie; Molloy, Elizabeth; Watterson, Leonie; Nestel, Debra
Abstract : Background: Simulation is reported as an appropriate replacement for a significant number of clinical hours in pregraduate programmes. To increase access for learners, educators have looked to understanding and improving learning in observer roles. Studies report equivalent learning outcomes and less stress in observer roles. However, reports on the prevalence, use and perceived value of observer roles from the educator's perspective are lacking. Methods: An exploratory survey for Australian and New Zealand (ANZ) simulation educators based on literature findings was developed and piloted with a small sample (n=10) of like subjects for language, clarity, skip logic and completion time. The final survey comprised 36 questions. Quantitative data were analysed using Pearson's chi-squared test, Welch's ANOVA and exploratory factor analysis. Select qualitative data were analysed using content analysis and summarised with frequency counts and categorisation. Results: Two hundred and sixty-seven surveys were completed, with 221 meeting criteria for analysis. The observer role is widely used in ANZ and most learners experience both hands-on and observer roles. The location of observers is dependent upon several factors including facility design, learner immersion, scenario design and observer involvement. Verbal briefings and/or other guides are provided to 89% of observers to direct their focus and 98% participate in the debrief. Educators value observer roles but tend to believe the best learning is hands-on. Conclusions: The learning in observer roles is less valued by educators than hands-on roles. Focused observation provides opportunities for noticing and attributing meaning, an essential skill for clinical practice. Learning spaces require consideration of scenario design and learning objectives. Scenario design should include objectives for observer roles and incorporate the observer into all phases of simulation. Attention to these areas will help promote the value of the different type of learning available in observer roles.